2003
DOI: 10.1074/jbc.m305385200
|View full text |Cite
|
Sign up to set email alerts
|

11,12-Epoxyeicosatrienoic Acid-induced Inhibition of FOXO Factors Promotes Endothelial Proliferation by Down-Regulating p27

Abstract: Cytochrome P450-derived epoxyeicosatrienoic acids (EETs) stimulate endothelial cell proliferation and angiogenesis. In this study, we investigated the involvement of the forkhead box, class O (FOXO) family of transcription factors and their downstream target p27Kip1 in EET-induced endothelial cell proliferation. Incubation of human umbilical vein endothelial cells with 11,12-EET induced a time-and dose-dependent decrease in p27Kip1 protein expression, whereas p21 Cip1 was not significantly affected. This effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
151
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(160 citation statements)
references
References 50 publications
9
151
0
Order By: Relevance
“…In agreement with our data, treatment of human endothelial cells with 11,12-EET leads to transient Akt activation (38), and this event seems to be related to the ability of this eicosanoid to induce EGF receptor phosphorylation (10). Moreover, treatment of bovine artery endothelial cells with 14,15-EET activates ERK1/2, which then stimulates the phosphorylation and activation of endothelial nitric-oxide synthase (39).…”
Section: 6-and 89-eet Promote Microvascular Endothelial Cell Migrasupporting
confidence: 78%
See 1 more Smart Citation
“…In agreement with our data, treatment of human endothelial cells with 11,12-EET leads to transient Akt activation (38), and this event seems to be related to the ability of this eicosanoid to induce EGF receptor phosphorylation (10). Moreover, treatment of bovine artery endothelial cells with 14,15-EET activates ERK1/2, which then stimulates the phosphorylation and activation of endothelial nitric-oxide synthase (39).…”
Section: 6-and 89-eet Promote Microvascular Endothelial Cell Migrasupporting
confidence: 78%
“…Our results suggest that these eicosanoids are capable of stimulating the same cell function by activating quite different cellular pathways. In this regard, it has been shown that the ability of 11,12-EET to induce endothelial cell proliferation results from PI3K/Akt-mediated down-regulation of the cyclin-dependent kinase inhibitor p27 kip1 (38). Moreover, studies with CYP2C9-transfected endothelial cells suggested that the mitogenic activity of 11,12-EET, one of the EETs formed by the enzyme (18), results from activation of the EGF receptor and subsequent PI3K/Akt-mediated activation (10).…”
Section: 6-and 89-eet Promote Microvascular Endothelial Cell Migramentioning
confidence: 99%
“…2B), an event that would be expected to decrease the p27Kip1 expression. 40,41 Indeed, there is also the question why the PI3K/AKT pathway, generally considered to be mitogenic, 42,43 is activated by 1,25D. We have experimentally confirmed that the downstream, pro-mitogenic targets of PI3K/AKT, GSK3β and p70S6K, are phosphorylated in concert with AKT (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…EETs are known to regulate vital physiological functions including vasoreactivity (23,24), inflammation (25), and cell proliferation (26,27). EETs have been considered to be candidates of endothelium-derived hyperpolarizing factors in human coronary vessel bed (23,28).…”
mentioning
confidence: 99%